Medical Cannabis for Gilles de la Tourette Syndrome: An Open-Label Prospective Study - Saar Anis; Corinne Zalomek; Amos D. Korczyn; Alina Rosenberg; Nir Giladi; Tanya Gurevich (Behavioural Neurology)
Objectives. Assessing the effectiveness and tolerability of medical cannabis (MC) treatment on Gilles de la Tourette syndrome (GTS) patients. Methods. We report on an open-label, prospective study on the effect of MC on adult GTS patients. MC mode of use was decided by the treating neurologist and the patient. Δ9-Tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD) content within MC product and monthly dose were titrated during the study. Following treatment initiation, patients were assessed after 4 and 12 weeks for efficacy, tolerability, and side effects. Results. Eighteen patients entered the study. Baseline Yale Global Tic Severity Scale- (YGTSS) Total (range 0-100) was 60.3±17.1. Three patients did not reach the end of follow-up period. The most common mode of administration was smoking (80%). Following twelve weeks of treatment, a significant 38% average reduction (p=0.002) of YGTSS-Total and a 20% reduction (p=0.043) of Premonitory Urge for Tic Scale (PUTS) were observed. Common side effects were dry mouth (66.7%), fatigue (53.3%), and dizziness (46.7%). Three patients suffered from psychiatric side effects including worsening of obsessive compulsive disorder (stopped treatment), panic attack, and anxiety (resolved with treatment modification). Six patients (40%) reported cognitive side effects regarding time perception, visuospatial disorientation, confusion, slow processing speed, and attention. Conclusions. MC treatment demonstrates good efficacy and tolerability in adult GTS patients. Predilection for smoking rather than using oil drops requires further comparative studies to evaluate the efficacy of each. Cognitive and psychiatric side effects have to be monitored and addressed.